1996
DOI: 10.1161/01.res.79.4.812
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Tissue Inhibitor of Matrix Metalloproteinase-1 Inhibits Vascular Smooth Muscle Cell Functions In Vitro and In Vivo

Abstract: Arterial smooth muscle cells (SMCs) are in a quiescent growth state under normal physiological conditions, but they can be stimulated to proliferate and migrate from one tissue compartment to another if the vessel is injured. This response might require a selective and focal increase in tissue degradation, which might be mediated through the increased production of matrix metalloproteinases (MMPs). Blockade of MMP activity might therefore inhibit the SMC response to injury. To test this hypothesis, we develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
110
2
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(121 citation statements)
references
References 54 publications
8
110
2
1
Order By: Relevance
“…Increased expression of both Ang II and endothelin-1 could be generated by RVCH in keeping with the properties of mast cell chymases. In addition, chymases can activate MMPs, which could facilitate SMC proliferation (35,36). Furthermore, cells stably transfected with RVCH have elevated collagen production (unpublished data).…”
Section: Discussionmentioning
confidence: 94%
“…Increased expression of both Ang II and endothelin-1 could be generated by RVCH in keeping with the properties of mast cell chymases. In addition, chymases can activate MMPs, which could facilitate SMC proliferation (35,36). Furthermore, cells stably transfected with RVCH have elevated collagen production (unpublished data).…”
Section: Discussionmentioning
confidence: 94%
“…Because TIMP-1 has been shown to inhibit SMCs proliferation 14 and TIMP-2 shows significant homology to erythroid growth factors and has been previously demonstrated to stimulate proliferation of some cell types, 22 we examined the effect of AdCMV.hTIMP-2 infection on the proliferation of cultured SMCs isolated from the neointima of ballooninjured rat carotid arteries. Figure 4 shows that there was no …”
Section: Effects Of Adcmvhtimp-2 On Cultured Smc Functionmentioning
confidence: 99%
“…5,13,14 Given the particular importance of MMP-2 to vessel injury and the fact that a unique association occurs between MMP-2 and TIMP-2, 15 we constructed a replication-deficient adenovirus encoding human TIMP-2 to infect cultured SMCs as well as SMCs in vivo and assess the effects of its expression on SMC function in cell culture and neointimal development after balloon withdrawal injury.…”
mentioning
confidence: 99%
“…This possibility is further supported by recent experiments with reseeding of SMC stably expressing TIMP-1 in the rat balloon injury model. 11 Our own previous studies have shown highly efficient transfer of the…”
Section: Introductionmentioning
confidence: 99%